2017
DOI: 10.1111/aor.12972
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Micropore‐Based Parallel Plate Membrane Oxygenator

Abstract: Extracorporeal membrane oxygenation (ECMO) is a life support system that circulates the blood through an oxygenating system to temporarily (days to months) support heart or lung function during cardiopulmonary failure until organ recovery or replacement. Currently, the need for high levels of systemic anticoagulation and the risk for bleeding are main drawbacks of ECMO that can be addressed with a redesigned ECMO system. Our lab has developed an approach using microelectromechanical systems (MEMS) fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Recently, some efforts have focused on improving the structural integrity of microfluidic devices. G, Dabaghi et al 136 uses a steel mesh to add rigidity to their PDMS membranes, and (H) Dharia et al 139 presents a device featuring rigid silicon micropore membranes bonded to a 5 µm PDMS layer. Images reproduced with permission from respective cited publications [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Application Of Novel Oxygenator Technology To the Artificialmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some efforts have focused on improving the structural integrity of microfluidic devices. G, Dabaghi et al 136 uses a steel mesh to add rigidity to their PDMS membranes, and (H) Dharia et al 139 presents a device featuring rigid silicon micropore membranes bonded to a 5 µm PDMS layer. Images reproduced with permission from respective cited publications [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Application Of Novel Oxygenator Technology To the Artificialmentioning
confidence: 99%
“…Another approach taken by Dharia and colleagues at UCSF used composite micropore-containing silicon and PDMS membranes. 139 The composite membranes offer the advantage of providing a rigid, yet, thin structure that can be readily stacked into a parallel plate configuration. Importantly, the parallel plate design allows optimization of the blood flow path to minimize shear stresses and stagnancy.…”
mentioning
confidence: 99%
“…Ajay Dharia et al of the University of California, San Francisco, CA, USA, reported on a silicon micropore‐based parallel plate oxygenator design. Their proof of concept study show adequate oxygen transport.…”
Section: Pulmonary Supportmentioning
confidence: 99%
“…The emergence of microfluidics technology presents an enormous opportunity to address many of the fundamental challenges in ECMO, due to the ability of microfluidics to fashion gas transfer membranes thinner than hollow fiber membrane oxygenators (HFMO), shallower blood channels, and potentially to better recapitulate the smooth and gentle manner in which blood flows through small vessels in the lung during the physiological gas transfer process [ 17 , 18 , 19 ]. Over the past decade, tremendous progress has been made by a number of groups in the development of microfluidic oxygenators, leveraging advances in computational designs, microfabrication techniques, and biomaterials technologies toward prototype devices that have been tested in vitro and in vivo in a large number of proof of concept studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%